Hormonal Priming Improves Seed Quality Parameters in Sunflower - Thakur, Ankita; Dilta, B. S.; Verma, Rohit; Kaushal, Sapna; Vinay (International Journal of Economic Plants, 2025)
The experiment was conducted during June–July 2021 at Department of Seed Science and Technology, Dr YS Parmar University of Horticulture and Forestry, Nauni, Solan (HP), to determine the effect of priming sunflower seeds at varying GA3 concentrations on the seed quality parameters. The sunflower seeds were subjected to different seed priming treatments with GA3. There were ten treatments with eight concentrations of GA3 @ 25, 50, 75, 100, 125, 150, 175, and 200 ppm and one of hydropriming, both for a duration of 12 hours along with control. From the study, it was observed that among all the treatments, treatment in which the seeds were primed with GA3 @100 ppm significantly enhanced the seed germination (92.50%), speed of germination (56.54), seedling length (28.20 cm), seedling fresh weight (582.20 mg), seedling dry weight (28.96 mg), SVI-I (2607.72), SVI-II (2678.51), oil content (43.99%) and resulted in the lowest EC (299.00 µS m-1). Whereas, minimum values for seed germination (76.75%), speed of germination (36.90), seedling length (22.94 cm), seedling fresh weight (445.48 mg), seedling dry weight (26.26 mg), SVI-I (1760.00), SVI-II (2014.77) and oil content (41.83%) as well as maximum seed electrical conductivity (444.75 µS m-1) was recorded in non-primed seeds (control). Consequently, it was concluded that seed primed with GA3 @ 100 ppm for 12 hours performed foremost amid all the treatments tested for seed quality parameters.